Medieval Ovid: Frame Narrative and Political Allegory - Gerber, A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2015)
Ovid's Metamorphoses played an irrefutably important role in the integration of pagan mythology in Christian texts during the Middle Ages. This book is the only study to consider this Ovidian revival as part of a cultural shift disintegrating the boundaries between not only sacred and profane literacy but also between academic and secular politics.
Keywords: Literature, Medieval; Classical literature; Literature—History and criticism; Civilization—History.; Medieval Literature; Classical and Antique Literature; Literary History; Cultural History